Parents' Beliefs and Behaviors About Their Children's Literacy Development: A Cross-Sectional Study in Saudi Arabia - AlAhmari, Fatimah Saeed (Frontiers in Pediatrics, 2022)
Background A home environment that promotes learning is a significant factor in school performance in which children's parents are involved in their education. However, little study has focused on parents' reading-related beliefs or the relationship between parents' literacy beliefs and behaviors. Methods This cross-sectional study describes the range of parents' reported literacy beliefs and behaviors and examines whether an association exists in Saudi Arabia. It was conducted on a convenient sample of 100 parents using a web-based self-administrated shared with families in Developmental and Behavioral Pediatrics clinics at multiple sites utilizing the Parents' Perceptions of Literacy Learning Interview Schedule (PPLLIS). Results There were 83 mothers and 17 fathers; 90% had a university degree or higher. Parents' beliefs ranged between 87 and 123, with a mean of 103.54 ± 8.05, indicating more holistic perceptions than skills-based ones. There was only a positive significant correlation between parents' beliefs and behaviors regarding literacy activities. However, those participating in literacy activities with their kids were more holistic parents and scored the top one-third on the PPLLIS. Conclusion Parents' beliefs and their reported behaviors are found to be significantly impacted by their educational levels. Therefore, future investigations and national campaigns are encouraged to improve parents' educational levels, especially in urban areas.